Prospek Introduksi Regulon nif dari Bakteri Klebsiella pneumoniae ke Dalam Genom Mitokondria Tanaman - Ivan Tjahja Pranata; Adminarwati Hulu; Yoga Aji Handoko (Politeknik Negeri Lampung., 2018)
Use of synthetic fertilizers bring environmental pollution, increase weed growth, reduceatmospheric oxygen levels, decrease the fertility of agricultural land, causing eutrophicationand run-offs, also even damaging coral reefs. Recent biotechnology approaches can beutilized to create a new variety of self-fertilization plants that allows it to supply its ownnitrogen making it possible to overcome nitrogen problems and avoid them. This reviewaims to understand how far genetic engineering approach can be used by the introduction ofnif regulon from Klebsiella penumoniae. The nitrogenase-encoding genes which make up thenif regulon proved can be inserted into the mitochondrial genome as like Allen et al. (2017)did in their research. The western blotting result showed that the research succesfullyintegrated the nif regulon to the genome and expressed their proteins.